N-Palmitoylethanolamine depot injection increased its tissue levels and those of other acylethanolamide lipids - Grillo SL; Keereetaweep J; Grillo MA; Chapman KD; Koulen P (Dove Medical Press, 2013)
Stephanie L Grillo,1,* Jantana Keereetaweep,2,* Michael A Grillo,1 Kent D Chapman,2 Peter Koulen1–3 1Vision Research Center, Department of Ophthalmology, School of Medicine, University of Missouri – Kansas City, Kansas City, MO, USA; 2University of North Texas, Center for Plant Lipid Research, Department of Biological Sciences, Denton, TX, USA; 3Department of Basic Medical Science, School of Medicine, University of Missouri – Kansas City, Kansas City, MO, USA *These authors contributed equally to this work Abstract: N-Palmitoylethanolamine (NAE 16:0) is an endogenous lipid signaling molecule that has limited water solubility, and its action is short-lived due to its rapid metabolism. This poses a problem for use in vivo as oral administration requires a high concentration for significant levels to reach target tissues, and injection of the compound in a dimethyl sulfoxide- or ethanol-based vehicle is usually not desirable during long-term treatment. A depot injection of NAE 16:0 was successfully emulsified in sterile corn oil (10 mg/kg) and administered in young DBA/2 mice in order to elevate baseline levels of NAE 16:0 in target tissues. NAE 16:0 levels were increased in various tissues, particularly in the retina, 24 and 48 hours following injections. Increases ranged between 22% and 215% (above basal levels) in blood serum, heart, brain, and retina and induced an entourage effect by increasing levels of other 18 carbon N-Acylethanolamines (NAEs), which ranged between 31% and 117% above baseline. These results indicate that NAE 16:0 can be used as a depot preparation, avoiding the use of inadequate vehicles, and can provide the basis for designing tissue-specific dosing regimens for therapies involving NAEs and related compounds. Keywords: cannabinoid receptor, vanilloid receptor, DBA/2 mice, lipid extraction, gas chromatography, mass spectrometry